Learn Aspen Plus in 24 Hours - Adams II, Thomas A. (McGraw-Hill's AccessEngineering., 2018)
Get started solving chemical engineering problems with Aspen Plus?! This practical guide shows, step-by-step, how to effectively work with Aspen Plus? in just 24 hours, with no experience required. Developed at McMaster University over a 7-year period, Learn Aspen Plus? in 24 Hours is divided into twelve 2-hour guided tutorials that equip you with the skills required to model and simulate a wide range of chemical processes rapidly?without performing tedious calculations.